Brasilianische Gewerkschaften im Aufwind? - Vellay, Claudius (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2003)
Twenty years after the raise of Brazilian "new unionism", this article analyses whether the unions in Brasilia had changed into authentic interest organisations of labour, Based on empirical evidence it will be argued, that the unionmovement today successfully left behind state-corporatism both in its structure and practice, The discussion of deficits and solutions, especially from the CUT model of firm-representation, will lead to suggestions for a reform of industrial relations, one of the central tasks of the new government of President Lula.